Pemetaan Potensi Simpanan Karbon Hutan Tanaman Industri Eucalyptus grandis di Hutan Tanaman Industri PT. Toba Pulp Lestari, Tbk., Sektor Aek Nauli - Titis Dian Pratama; Siti Latifah; Pindi Patana (Program studi Kehutanan USU, 2013)
Industrial Forest Plantation when viewed from storing carbon productivity (per unit area and per unit time) then there is a possibility of plantations will have the ability to store carbon in their stend in greater numbers than in natural forests because they have shorter cycle. The purpose of this study was to investigate and mapping the potential content of biomass, carbon storage and uptake of CO2 of Eucalyptus grandis stends Industrial Forest Plantation in PT. Toba Pulp Lestari Tbk. Sector Aek Nauli, Simalungun District, North Sumatra. The method of data calculation was using the model Allometric of Eucalyptus spp stand.There are four species of eucalyptus met at PT. Toba Pulp Lestari Tbk. Aek Nauli sector namely Eucalyptus hybrid, Eucalyptus grandis, Eucalyptus pelita and Eucalyptus urophylla.The results showed total biomass in Eucalyptus grandis has amounted to 8,4528 tons/ha, carbon storage at 3,8759 tons/ha, and absorption of CO2 at 14,2245 tonsCO2/ha. Key words: Eucalyptus grandis, Industrial Forest Plantation, PT. Toba Pulp Lustari, Carbon Saving,